PROJECTED EXTREME RAINFALL INDICES IN GUINEA AND SUDANO-SAHELIAN ECOLOGICAL ZONES, NIGERIA - Salihu, A. C.; Abdulkadir, A.; Nsofor, G. N.; Otache, M. Y. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2020)
Drought and Flood episodes are twin issues that are consequences of extreme rainfall events. The negative impact of extreme rainfall events makes understanding their behaviour under the future climate change necessary for regional planning. Hence, the objective of the study is to project extreme rainfall indices in Guinea and Sudano-Sahelian ecological zones, Nigeria. A set of four extreme rainfall indices namely: maximum 5-day rainfall (Rx5day), heavy rainfall days (R10mm), consecutive wet days (CWD) and consecutive dry days (CDD) were adopted. The data and computation were done using KNMI Climate Explorer. Projections were produced for the near-term 2019-2048, mid-term 2049-2078 and long-term 2079-2100 periods with reference to the 1959-1988 and 1989-2018 baselines. The multi-model ensemble mean of couple model intercomparison project 5 (CMIP5) under representative concentration pathways (RCPs) 2.6, 4.5, and 8.5 were used. Mann-Kendal statistical test was adopted to analyze the trends in extreme rainfall indices at the 0.05 significance level. Based on the results, it can be deduced that there is a significant positive trend in the whole Guinea and Sudano-Sahelian ecological zone as a region for maximum 5-day rainfall with respect to all the three RCPs. As for heavy rainfall, itreveals that there is no significant positive trend for RCP2.6 with respect to the three projected periods under consideration but significant positive trends with respect to 2049-2078 for RCP4.5 as well as RCP8.5 with respect to 2049-2078 and 2079-2100 periods. Increase in CDD, as well as a decrease in CWD, were both not significant at the 0.05 confidence level. Therefore, it is expected that this study will aid guidance to the understanding of the ongoing changes as well as possible changes in rainfall and rainfall-related extremes. It is also important for future planning of water resources management and agriculture in Guinea and Sudano-Sahelian ecological zones of Nigeria.
Keywords: Extreme rainfall indices, Guinea, Sudano-Sahelian, Ecological zones, Nigeria